Preparation method of Cu < + >-based loaded dual-MOF composite material

By preparing Cu+-based loaded dual MOF composite materials, the in-situ growth technology of ZIF-8 and Cu-BTC was used to solve the problems of CO gas capture and recovery in industrial production, and efficient and stable CO adsorption performance was achieved.

CN119633773APending Publication Date: 2025-03-18SHANDONG UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411841118.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the capture and recovery of CO gases in industrial production, especially while maintaining high adsorption capacity, rapid adsorption speed, stability and selectivity.

Method used

The preparation method of Cu+-based loaded dual MOF composite was adopted, and the high-stability ZIF-8 was prepared as the core MOF material by hydrothermal synthesis, and the in-situ uniform growth of Cu-BTC was achieved in organic solvents. Finally, the Cu+-based loaded dual MOF composite was prepared by impregnation.

Benefits of technology

It has achieved CO adsorption performance with large adsorption capacity, fast adsorption speed, good stability and good selectivity, and is suitable for CO adsorption control in most industrial environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633773A_ABST
    Figure CN119633773A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Cu < + >-based loaded dual-MOF (Metal Organic Framework) composite material, which is a dual-MOF adsorption material prepared by taking high-stability ZIF-8 as a core, Cu-BTC as a growth layer and methanol as a growth environment. The method comprises the following steps: preparing high-stability ZIF-8 as a core MOF material, and adding a metal organic framework and an inorganic ligand into an organic solvent to realize in-situ uniform growth of Cu-BTC; a normal-temperature impregnation method is adopted, CuCl is used as a loading material, and the Cu < + >-based loaded dual-MOF composite material is prepared. By utilizing sp2 hybridization of CO functional groups, the CO adsorption performance is improved through pi-pi interaction. The preparation process is simple, easy to operate and low in equipment requirement, the production cost and difficulty are reduced, and the adsorbent has excellent adsorption properties such as large CO adsorption capacity, high adsorption speed, good stability and good selectivity; the catalyst is suitable for CO adsorption treatment in most industrial environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal organic framework materials and specifically relates to a Cu + Preparation method of substrate-supported dual MOF composite materials. Background Art

[0002] As a toxic and harmful gas, CO is widely present in industrial production and energy applications. If the CO tail gas generated in industrial production is not treated in time and discharged into the atmosphere to react and generate chemical smog, it will have an impact on the environment and even endanger human health. However, in chemical, metallurgical and other industrial production, CO plays an important role as a raw material. Carbon capture, recycling and conversion of CO gas is one of the main measures to prevent and control CO pollution. The application of different separation technologies to separate CO from different gases in industrial production and continue to be applied to production in other industries has important research value. The adsorption method for recovering and separating CO is easy to operate and has low cost. The π complex bond belongs to the special weak chemical bond category by complex adsorption. The π complex force is much stronger than the van der Waals force of physical adsorption, so it shows strong gas selectivity and can be used as an effective way to adsorb CO. Cu + With (n-1)d 10 ns 0 The electronic configuration of α-C makes it easy to accept electrons, and the fully occupied d orbital is also easy to donate electrons, forming σ-π bonds with CO. The synergistic effect between bonds can enhance the interaction between metal and adsorbate molecules. It is considered to be a promising complex adsorption strategy and is of great significance for the development of complex adsorption materials with high CO adsorption capacity and selectivity.

[0003] Metal-organic frameworks (MOFs), as a new type of organic-inorganic hybrid / composite crystalline microporous solids, are adsorbents with the advantages of ordered porous structure, open metal sites, complex composition, and high specific surface area. MOFs containing open or coordinatively unsaturated metal sites (OMS) are conducive to the isomerization reaction of guest molecules and broaden the application of MOFs in gas adsorption. Among the commonly used MOFs with unsaturated metal center sites, Cu-BTC (Cu 2+ ) can be changed without affecting the central structure and is widely used in the field of gas adsorption due to its relatively easy synthesis, large specific surface area, good crystallinity, high porosity and low cost. Investigations and studies have found that ZIF-8 can maintain a complete crystal structure in water for more than 15 days, showing excellent water stability. ZIF-8 is a typical zeolite imidazole framework material composed of a tetrahedral transition metal Zn 2+ It is formed by self-assembly of ions and imidazolate molecules as organic linkers. It is easy to synthesize, easy to functionalize, and has good stability. It is an excellent gas adsorption material with broader application prospects. Summary of the invention

[0004] In order to solve the above problems, the present invention proposes a Cu + The invention uses high-stability ZIF-8 as the core, macroporous Cu-BTC as the growth layer, and methanol as the growth environment to prepare Cu + The dual MOF adsorption material is evenly distributed and grown, in order to achieve excellent adsorption properties such as large adsorption capacity, fast adsorption speed, good stability and good selectivity.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A Cu + The preparation method of the base-supported dual MOF composite material comprises the following steps:

[0007] S1. Prepare the core ZIF-8 of MOF-A by hydrothermal synthesis;

[0008] S2, using MOF-B material Cu-BTC as the growth layer, Cu-BTC@ZIF-8 was prepared by in-situ growth method;

[0009] S3. Using monovalent Cu as the loading material, an impregnation method was used to prepare a Cu-based dual-MOF composite material in which MOF-B was uniformly grown in situ on MOF-A.

[0010] Preferably, in S1, the specific steps of preparing ZIF-8 are:

[0011] Zn(NO3)2·6H2O and dimethylimidazole were mixed in methanol organic solvent. 2+ The solvent is slowly added dropwise to the dimethylimidazole solution and stirred at room temperature for 10-60 minutes. The obtained material is aged at room temperature for 10-30 hours and then centrifuged, washed with an organic solvent and dried to obtain a powdery product.

[0012] Preferably, in S2, the specific preparation method of Cu-BTC is:

[0013] Cu(NO3)2·3H2O and H3BTC were simultaneously dissolved in the methanol organic solvent of ZIF-8 and stirred evenly to obtain a coating. Uniform growth of Cu-BTC was achieved under hydrothermal conditions, and then washed and dried with an organic solvent to obtain uniformly grown Cu-BTC@ZIF-8 blue powder.

[0014] Preferably, the hydrothermal temperature is 50-150° C. and the duration is 10-30 h.

[0015] Preferably, in S3, the Cu-BTC@ZIF-8 obtained in S2 is mixed with the CuCl solution and stirred at room temperature for 30 min to complete the Cu+ The Cu-BTC@ZIF-8 material was prepared by using Cu-based loading.

[0016] Preferably, the molar ratio of Zn(NO3)2·6H2O to dimethylimidazole is 0.3-2;

[0017] Preferably, the molar ratio of Cu(NO3)2·3H2O to H3BTC is 0.5-2.5;

[0018] Preferably, the mass ratio of MOF-A to MOF-B is 50%-200%.

[0019] Preferably, the mass ratio of CuCl to Cu-BTC@ZIF-8 is 10%-50%.

[0020] The present invention also proposes a Cu + The double MOF composite material supported by the substrate is prepared by the method mentioned above. The double MOF composite material is used in harmful gas treatment to adsorb CO in the harmful gas.

[0021] Compared with the prior art, the present invention provides a Cu + The preparation method of the base-loaded dual MOF composite material has the following beneficial effects:

[0022] (1) The preparation process of the dual MOF composite material proposed in this application is simple, easy to operate, and has low equipment requirements, which reduces the production cost and difficulty. It combines two different MOFs to construct an unprecedented MOF-on-MOF nanostructure, providing a research idea for improving gas adsorption performance.

[0023] (2) The present application first prepares highly stable ZIF-8 as the core MOF material, then adds metal organic frameworks and inorganic ligands into an organic solvent to achieve in-situ uniform growth of Cu-BTC; and adopts a room temperature impregnation method with CuCl as the loading material to prepare Cu + Dual MOF composites supported on a substrate. 2 Hybridization, increasing CO adsorption performance through π-π interaction, prepared Cu + The evenly distributed and grown dual-MOF adsorption material has excellent adsorption properties for CO, such as large adsorption capacity, fast adsorption speed, good stability and good selectivity; it is suitable for CO adsorption treatment in most industrial environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0025] Figure 1 The morphology of the Cu-based double MOF prepared in Example 4 of the present invention is shown in FIG.

[0026] Figure 2 This is the CO adsorption diagram of the Cu-based dual MOF prepared in Example 4 of the present invention.

[0027] Figure 3 This is a multi-component penetration diagram of the Cu-based dual MOF prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] A Cu + The preparation method of the dual MOF composite material loaded with the base is as follows: first, 2.58g Zn(NO3)2·6H2O and 2.63g dimethylimidazole are dissolved in 100mL methanol. The dimethylimidazole solution is added dropwise to Zn 2+ The solution was stirred magnetically at room temperature for 30 min and then aged at room temperature for 24 h to produce a white solid. In order to obtain the expected resulting crystals, the prepared solution was centrifuged, washed with methanol for multiple times, and finally dried in a vacuum oven for 24 h to obtain a white powder.

[0031] 2.0g white powder and 1.126g Cu(NO3)2·3H2O were dispersed in 150ml methanol solvent, and 0.56g ligand trimesic acid was added and stirred to obtain the coating. The in-situ growth of Cu-BTC was achieved under hydrothermal conditions at 70℃ for 24h, followed by cross-washing with water and methanol three times, and finally dried at 60℃ in a vacuum drying oven to obtain the product. 1g Cu-BTC@ZIF-8 was mixed with 0.2g CuCl solution (1mol / L), and then stirred at room temperature for 30min to complete the Cu + The final material was obtained by drying at 60 °C. The CO adsorption capacity of the sample was studied by a BET instrument (BSD-660MA6M). Before the test, a sample of a specified weight (about 300 mg) was placed in a sample tube for degassing. The sample was degassed in N2 at 423K for 2h to purge moisture and dust in the sample, so that the CO and other impurities adsorbed in the sample air were desorbed and reached a pure state. The test result is a CO adsorption isotherm with a pressure range of 0.7-100 kPa and a temperature of 298K. Test Cu+ The specific surface area of ​​the dual MOF composite material supported by the substrate is 396.3 m 2 / g, and the CO adsorption performance is 2.01mmol / g.

[0032] Example 2

[0033] A Cu + The preparation method of the dual MOF composite material loaded with the base is as follows: first, 2.58g Zn(NO3)2·6H2O and 2.37g dimethylimidazole are dissolved in 100mL methanol. The dimethylimidazole solution is added dropwise to Zn 2+ The solution was stirred magnetically at room temperature for 10 min and then aged at room temperature for 10 h to produce a white solid. In order to obtain the expected resulting crystals, the prepared solution was centrifuged, washed with methanol for multiple times, and finally dried in a vacuum oven for 24 h to obtain a white powder.

[0034] 2.0g white powder and 4.0g Cu(NO3)2·3H2O were dispersed in 150ml methanol solvent, and 3.979g ligand trimesic acid was added and stirred to obtain the coating. The in-situ growth of Cu-BTC was achieved under hydrothermal conditions at 50℃ for 10h, followed by cross-washing with water and methanol three times, and finally dried in a vacuum drying oven at 60℃ to obtain the product. 1g Cu-BTC@ZIF-8 was mixed with 0.1g CuCl solution (1mol / L), and then stirred at room temperature for 30min to complete the Cu + The final material was obtained by drying at 60 °C. The CO adsorption capacity of the sample was studied by a BET instrument (BSD-660MA6M). Before the test, a sample of a specified weight (about 300 mg) was placed in a sample tube for degassing. The sample was degassed in N2 at 423K for 2h to purge moisture and dust in the sample, so that the CO and other impurities adsorbed in the sample air were desorbed and reached a pure state. The test result is a CO adsorption isotherm with a pressure range of 0.7-100 kPa and a temperature of 298K. Test Cu + The specific surface area of ​​the dual MOF composite material supported by the substrate is 102.1 m 2 / g, and the CO adsorption performance is 0.86mmol / g.

[0035] Example 3

[0036] A Cu + The preparation method of the dual MOF composite material loaded with the base material is as follows: first, 2.58g Zn(NO3)2·6H2O and 0.356g dimethylimidazole are dissolved in 100mL methanol. The dimethylimidazole solution is added dropwise to Zn 2+The solution was stirred magnetically at room temperature for 60 min and then aged at room temperature for 30 h to produce a white solid. In order to obtain the expected resulting crystals, the prepared solution was centrifuged, washed with methanol for multiple times, and finally dried in a vacuum oven for 24 hours to obtain a white powder.

[0037] 2.0g white powder and 1.0g Cu(NO3)2·3H2O were dispersed in 150ml methanol solvent, and 0.199g ligand trimesic acid was added and stirred to obtain a coating. The in-situ growth of Cu-BTC was achieved under hydrothermal conditions at 150℃ for 30h, followed by cross-washing with water and methanol three times, and finally dried in a vacuum drying oven at 60℃ to obtain the product. 1g Cu-BTC@ZIF-8 was mixed with 0.5g CuCl solution (1mol / L), and then stirred at room temperature for 30min to complete the Cu + The final material was obtained by drying at 60 °C. The CO adsorption capacity of the sample was studied by a BET instrument (BSD-660MA6M). Before the test, a sample of a specified weight (about 300 mg) was placed in a sample tube for degassing. The sample was degassed in N2 at 423K for 2h to purge moisture and dust in the sample, so that the CO and other impurities adsorbed in the sample air were desorbed and reached a pure state. The test result is a CO adsorption isotherm with a pressure range of 0.7-100 kPa and a temperature of 298K. Test Cu + The specific surface area of ​​the dual MOF composite material supported by the substrate is 124.5 m 2 / g, and the CO adsorption performance is 1.03mmol / g.

[0038] Example 4

[0039] A Cu + The preparation method of the dual MOF composite material loaded with the base is as follows: first, 2.58g Zn(NO3)2·6H2O and 2.63g dimethylimidazole are dissolved in 100mL methanol. The dimethylimidazole solution is added dropwise to Zn 2+ The solution was stirred magnetically at room temperature for 45 min and then aged at room temperature for 24 h to produce a white solid. In order to obtain the expected resulting crystals, the prepared solution was centrifuged, washed with methanol for multiple times, and finally dried in a vacuum oven for 24 h to obtain a white powder.

[0040] 2.0g white powder and 1.126g Cu(NO3)2·3H2O were dispersed in 150ml methanol solvent, and 0.56g ligand trimesic acid was added and stirred to obtain the coating. The in-situ growth of Cu-BTC was achieved under hydrothermal conditions at 60℃ for 20h, followed by cross-washing with water and methanol three times, and finally dried in a vacuum drying oven at 60℃ to obtain the product. 1g Cu-BTC@ZIF-8 was mixed with 0.25g CuCl solution (1mol / L), and then stirred at room temperature for 30min to complete the Cu + The final material was obtained by drying at 60 °C. The CO adsorption capacity of the sample was studied by a BET instrument (BSD-660MA6M). Before the test, a sample of a specified weight (about 300 mg) was placed in a sample tube for degassing. The sample was degassed in N2 at 423K for 2h to purge moisture and dust in the sample, so that the CO and other impurities adsorbed in the sample air were desorbed and reached a pure state. The test result is a CO adsorption isotherm with a pressure range of 0.7-100 kPa and a temperature of 298K. Test Cu + The specific surface area of ​​the dual MOF composite material supported by the substrate is 378.4 m 2 / g, with Figure 1 The porous morphology shown corresponds to the CO adsorption performance of 2.16mmol / g. Figure 2 As shown, it exhibits a higher adsorption level than other materials. Multi-component performance tests were conducted before and after mixing with CuCl solution ( Figure 3 ) found that the adsorption selectivity of CO was significantly improved.

[0041] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A method for preparing a Cu+-based dual MOF composite material, characterized in that: The steps are as follows: S1. Prepare the core ZIF-8 of MOF-A by hydrothermal synthesis; S2, using MOF-B material Cu-BTC as the growth layer, Cu-BTC@ZIF-8 was prepared by in-situ growth method; S3. Using monovalent Cu as the loading material, an impregnation method was used to prepare a Cu-based dual-MOF composite material in which MOF-B was uniformly grown in situ on MOF-A.

2. The method for preparing a Cu+-supported dual MOF composite material according to claim 1, characterized in that: In S1, the specific steps for preparing ZIF-8 are: Zn(NO3)2·6H2O and dimethylimidazole were mixed in methanol organic solvent. 2+ The solvent is slowly added dropwise to the dimethylimidazole solution and stirred at room temperature for 10-60 minutes. The obtained material is aged at room temperature for 10-30 hours and then centrifuged, washed with an organic solvent and dried to obtain a powdery product.

3. The method for preparing a Cu+-supported dual MOF composite material according to claim 2, characterized in that: In S2, the specific preparation method of Cu-BTC is: Cu(NO3)2·3H2O and H3BTC were simultaneously dissolved in the methanol organic solvent of ZIF-8 and stirred evenly to obtain a coating. Uniform growth of Cu-BTC was achieved under hydrothermal conditions, and then washed and dried with an organic solvent to obtain uniformly grown Cu-BTC@ZIF-8 blue powder.

4. The method for preparing a Cu+-supported dual MOF composite material according to claim 3, characterized in that: The hydrothermal temperature is 50-150°C and the duration is 10-30h.

5. The method for preparing a Cu+-supported dual MOF composite material according to claim 1, characterized in that: In S3, the Cu-BTC@ZIF-8 obtained in S2 was mixed with the CuCl solution and stirred at room temperature for 30 min to complete the Cu + The Cu-BTC@ZIF-8 material was prepared by using Cu-based loading.

6. The method for preparing a Cu+-supported dual MOF composite material according to claim 2, characterized in that: The molar ratio of Zn(NO3)2·6H2O to dimethylimidazole is 0.3-2.

7. The method for preparing a Cu+-supported dual MOF composite material according to claim 3, characterized in that: The molar ratio of Cu(NO3)2·3H2O to H3BTC is 0.5-2.

5.

8. The method for preparing a Cu+-supported dual MOF composite material according to claim 3, characterized in that: The mass ratio of MOF-A to MOF-B is 50%-200%.

9. The method for preparing a Cu+-supported dual MOF composite material according to claim 5, characterized in that: The mass ratio of CuCl to Cu-BTC@ZIF-8 is 10%-50%.

10. A kind of Cu + The double MOF composite material supported by the substrate is prepared by the method according to any one of claims 1 to 9, characterized in that: The dual MOF composite material is used in harmful gas treatment to adsorb CO in harmful gases.

Citation Information

Cited By

  • Cu / Zn bimetal organic framework catalyst and application thereof

    CN120485864A